Economics - Sloman, John, 1947- (Pearson Education, 2022)
"Now in its 10th edition, Economics by Sloman, Garratt & Guest is known and loved for its active learning, student-friendly approach and unrivalled lecturer and student support. Ithas been specially updated for 2020/21 to take into account the latest developments in the global economy, including the effects of the Covid-19pandemic".